THE USE OF HAND PUPPET IN TEACHING NARRATIVE TEXT - Kulaan, Yashinta Diajeng; Yuliana, Yohanes Gatot Sutapa; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is entitled ?The Use of Hand Puppet in Teaching Narrative Text?. The purpose of this research is to find out whether the use of hand puppet affects significantly or not to the students? ability in speaking narrative textand to find the effect size of hand puppet in affect students? ability in speaking narrative text.In conducting this research, the writer applied pre-experimental research using one sample group. The population of this research was Eighth grade of Junior High School 4 Sungai Raya academic year 2018/2019, and the sample was taken from the students of class 8B that consist of 29 students.Furthermore, the research indicated that the effect size (0.93) was categorized as high. The calculation of t-obtained (26.51) was higher than t-table (2,048). In conclusion, the alternate hypothesis ?The use of hand puppet affects significantly to the students? ability in speaking narrative text? was accepted and the null hypothesis ?The use of hand puppet does not affect significantly to the students? ability in speaking narrative text? was rejected.  Key words: Hand Puppet, Narrative Text, Teaching Narrative